QOL-01. LONGITUDINAL COMPARISON OF NEUROCOGNITIVE TRAJECTORIES IN PEDIATRIC MEDULLOBLASTOMA PATIENTS TREATED WITH PROTON VERSUS PHOTON RADIOTHERAPY. (4th December 2020) - Kahalley, Lisa; Peterson, Rachel; Ris, M Douglas; Janzen, Laura; Okcu, M Fatih; Grosshans, David; Ramaswamy, Vijay; Paulino, Arnold; Hodgson, David; Mahajan, Anita; Tsang, Derek; Laperriere, Normand; et al.
Abstract: PURPOSE: By reducing dose to normal brain tissue, proton radiotherapy (PRT) may lessen neurocognitive risk traditionally associated with photon radiotherapy (XRT). We examined change in neurocognitive scores over time in pediatric medulloblastoma patients treated with PRT versus XRT. METHODS: Neurocognitive scores from 79 patients (37 PRT, 42 XRT) were examined. Patients were treated between 2007–2018 on the same treatment protocols that differed only by craniospinal modality (PRT versus XRT). Change in scores over time since diagnosis were compared between groups. RESULTS: Groups were similar on most demographic/clinical variables: sex (67.1% male), age at diagnosis (mean 8.6 years), CSI dose (median 23.4 Gy), length of follow-up (mean 4.3 years), and parental education (mean 14.3 years). Boost dose ( p <0.001) and margin ( p =0.001) differed between groups. Adjusting for covariates, the PRT group exhibited superior outcomes in global IQ, perceptual reasoning, and working memory versus the XRT group (all p <0.05). The XRT group exhibited significant decline in global IQ, working memory, and processing speed (all p <0.05). The PRT group exhibited stable scores in all domains except processing speed ( p =0.003). Posterior fossa syndrome imparted risk independent of modality. CONCLUSION: This is the first study comparing neurocognitive trajectories between pediatric patients treated for medulloblastoma with PRT versus XRT on comparable, contemporary protocols. PRT was associated with more favorable neurocognitive outcomes in most domains compared to XRT, although processing speed emerged as vulnerable in both groups. This is the strongest evidence to date of an intellectual sparing advantage with PRT in the treatment of pediatric medulloblastoma.